The Physical Profile Of High-level Handball Players In Algeria According To Playing Positions - Benaissa, Fayssal (Journal of Sport Science Technology and Physical Activities, 2024)
The Object of the study aims to identify the physical profile of high-level handball players in Algeria, according to playing positions for this purpose, we used the method descriptive On a sample composed of of 44 handball players from the premier division Chosen as a random stratified manner, and for data collection, we used a tool a set of physical tests as a research tool After collecting the results and having treated them statistically, we conclude the physical profile of handball players, the high level varies according to the playing positions.On this basis, the study recommended the derived profile serves as a database for identifying the characteristics of each position physically and comparing them - in the future - with international standards in order to assess the local players' level and plan specialized training.